Crouzon syndrome with acanthosis nigricans: A case report and literature review - Quan Duy Nguyen; Tu Nguyen Anh Tran; Hao Trong Nguyen (PAGEPress Publications, 2022)
Crouzon's syndrome with acanthosis nigricans is an autosomal dominant disease, with typical features of classic Crouzon craniosynostosis, verrucous hyperplasia, and hyperpigmentation of the skin. While several mutations in FGFR2 cause classic Crouzon syndrome, Crouzon syndrome with acanthosis nigricans results from a point mutation in the fibroblast growth factor receptor 3 gene (FGFR3). We report an 8-year-old Vietnamese girl diagnosed with Crouzon syndrome with acanthosis nigricans, showing typical clinical features, including a crouzonoid face and dark plaques on skin. Genetic testing showed a missense variation in FGFR3, associated with Crouzon syndrome with acanthosis nigricans. Following diagnosis, we treated acanthosis nigricans with 10% urea cream. This case study and literature review discusses the cutaneous manifestations and dermatological treatments, while demonstrating the importance of clinical examination and evaluation of the patient's medical history during diagnosis. Our findings contribute to the global pool of data, providing practical insights into the manifestations of Crouzon syndrome.